Introduction: Sustainable shipping and transport logistics in developing economies - Jabbour, Charbel José Chiappetta [UNESP]; De Sousa Jabbour, Ana Beatriz Lopes [UNESP]; Yong, Geng; Tiwari, Manoj Kumar (Inderscience Publishers, 2015)
Considering the relevance and challenges of managing shipping and transport logistics for sustainable development in developing economies, this special issue presents a group of fresh, high-quality empirical evidence for the state-of-the-art. Research results from Brazil, India and China are presented, in order to offer readers an up-to-date view on the barriers, opportunities, propositions and useful insights for scholars, practitioners, and researchers. Finally, we present key subjects for a research agenda on sustainable shipping and transport logistics in developing economies.
Keywords: emerging economies; sustainable development; sustainable logistics; sustainable shipping; sustainable transport